A Lanthipeptide‐like N‐Terminal Leader Region Guides Peptide Epimerization by Radical SAM Epimerases: Implications for RiPP Evolution. (1st September 2016) - Fuchs, Sebastian W.; Lackner, Gerald; Morinaka, Brandon I.; Morishita, Yohei; Asai, Teigo; Riniker, Sereina; Piel, Jörn
Abstract: Ribosomally synthesized and posttranslationally modified peptide natural products (RiPPs) exhibit diverse structures and bioactivities and are classified into distinct biosynthetic families. A recently reported family is the proteusins, with the prototype members polytheonamides being generated by almost 50 maturation steps, including introduction ofd ‐residues at multiple positions by an unusual radical SAM epimerase. A region in the protein‐like N‐terminal leader of proteusin precursors is identified that is crucial for epimerization. It resembles a precursor motif previously shown to mediate interaction in thioether bridge‐formation in class I lanthipeptide biosynthesis. Beyond this region, similarities were identified between proteusin and further RiPP families, including class I lanthipeptides. The data suggest that common leader features guide distinct maturation types and that nitrile hydratase‐like enzymes are ancestors of several RiPP classes.